(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The National Health Policy 2017 (NHP-2017) aspires to avail or provide all Indians with high-quality reasonably priced healthcare services and universal coverage of health. The aim of this program, which has played an important or significant role in forming India’s healthcare system, are in queue with the idea of universal health insurance. The National Health Protection Scheme and Health and Wellness Centres are the two main and very important pillars of the Ayushman Bharat Program, which was unveiled in the financial budget for 2018-19 and expands upon the NHP-2017. The program aims to increase the availability, accessibility, and affordability of primary, secondary, and tertiary healthcare services in India. Research has shown that the scheme (Ayushman Bharat) has played an important role in managing and mitigating the COVID-19 outbreak in India. The program has created the necessary infrastructure to provide free healthcare to millions of Indians, including free testing and treatment in empanelled hospitals, as well as benefits like transportation for healthcare workers. Since its launch in 2018, the Ayushman Bharat Program has provided free treatment to more over 2 crore individuals, among other noteworthy accomplishments. It’s evident that the initiative has been crucial in combating the pandemic, and that it might be or seem to be have been very difficult to control the outbreak without it. All things considered, the Ayushman Bharat Program and the National Health Policy of 2017 have played a crucial or significant role in bolstering India’s healthcare system and offering millions of Indians access to reasonably priced medical care.